RISKS IN THE SYSTEM OF MANAGEMENT DECISION-MAKING AT THE ENTERPRISE - TARLOPOV, Іhor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the work is to identify the risks in the management decision-making system at the enterprise. The definition of the risk is opposed to uncertainty that arises when events cannot be classified by objective probabilities, but instead associated with subjective probabilities in the form of degree of confidence of economic agents. The features of the following risk groups are determined: internal and external. The following internal risks are considered: operating, financial, marketing, professional, strategic, reputational. The features of the following types of external risks are considered: financial, economic, correspondence, technological, environmental. The risks of activity and goals of sustainable development have been analyzed. An iterative process that is repeated for each category of losses in the past, present and future, crossing understanding, interpretation and use, can increase the competitiveness of the firm, working in two ways. On the one hand, by increasing organizational flexibility, that is, the ability to effectively respond to both endogenous and exogenous critical situations, through adaptation to high stressful situations. On the other hand, stimulating organizational stability, that is, the agility to quickly transform operations to solve adverse situations with a positive prognosis. With the conceptual model proposed in this paper, based on a systematic review of the literature and interpretive hermeneutics, it is thereby possible to integrate both the strategic and the technical operational attributes of risk. It offers a broad insight, both quantitatively and qualitatively, into the influence of risk on the competitive, corporate and social dynamics of the company. Based on this conceptual instrument, a concrete risk management tool is developed that relates the different sources of risk to the different aspects of sustainability.
Keywords: Risk; sustainable development; strategy; uncertainty; economic agent